Implementation of The Teaching Tool Feature in Learning Plane Geometry For 2nd Grade at Sekolah Penggerak - Hapsari, Ririk Woro; Matsuri, Matsuri; Supianto, Supianto (Social, Humanities, and Educational Studies (SHES): Conference Series, 2025)
The Platform merdeka mengajar is one of the tools created by the government to facilitate teachers in understanding and implementing the kurikulum merdeka in the learning process. However, in practice, many schools have not yet utilized the Platform merdeka mengajar appropriately; teachers are not using the platform in either the planning or implementation stages of learning. The Platform merdeka mengajar has a teaching materials feature that teachers can use as a reference when preparing for instruction. This research aims to describe the implementation of the teaching materials feature in learning activities, specifically for the topic of 2D shapes in the second grade. This study employed a case study method with a descriptive qualitative approach. Data were collected through interviews, observation, and documentation. The results of this study indicate that the Platform merdeka mengajar can be implemented in the planning, implementation, and assessment stages of learning. The teaching materials feature provides resources that include CP/ATP, teaching modules, student worksheets, and evaluation instruments. Based on the research conducted, it can beconcluded that the Platform merdeka mengajar can assist teachers in implementing the kurikulum merdeka in the teaching and learning process.